2021
DOI: 10.3389/fpsyt.2021.751215
|View full text |Cite
|
Sign up to set email alerts
|

A Review on P300 in Obsessive-Compulsive Disorder

Abstract: Neuropsychological studies indicate the presence of cognitive changes in patients with obsessive-compulsive disorder (OCD). Indeed, OCD may be included among the dysfunctions of the frontal lobes and their connections with the limbic system, associative cortex, and basal ganglia. P300 is a positive component of the human event-related potential (ERP); it is associated with processes of encoding, identification, and categorization constituting, as a whole, the superior cortical function of information processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 100 publications
(388 reference statements)
0
6
0
Order By: Relevance
“…It may be uneasy to reconcile these two theories, given that many studies report opposite results. As proposed in a review, the differences noted across studies may be explained by the severity of OCD symptoms, where greater severity is linked to a decrease in the amplitude of the P300 [117], which could feature the impact of OCD symptoms on processes mediated through the prefrontal cortical regions, which are hypothesized to be involved in memory inhibition mechanisms [118]. Moreover, Thibault et al [43] observed that a higher severity level correlates with a more significant decrease in the P300 component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be uneasy to reconcile these two theories, given that many studies report opposite results. As proposed in a review, the differences noted across studies may be explained by the severity of OCD symptoms, where greater severity is linked to a decrease in the amplitude of the P300 [117], which could feature the impact of OCD symptoms on processes mediated through the prefrontal cortical regions, which are hypothesized to be involved in memory inhibition mechanisms [118]. Moreover, Thibault et al [43] observed that a higher severity level correlates with a more significant decrease in the P300 component.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Thibault et al [43] observed that a higher severity level correlates with a more significant decrease in the P300 component. Thus, it is plausible that the decrease in P300 is caused by greater symptom severity, whereas the increase in P300 is observed more in patients with less severe symptoms [117].…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychological studies indicate that patients with OCD may present impairments in cognitive control functions involving executive control, information coding, motor and cognitive inhibition, and processing speed (Raggi et al, 2021). Neuroimaging studies associated these impairments with disturbances in brain networks including the PFC, the SMA, basal ganglia, the subthalamic nucleus and the inferior parietal lobe (Carlisi et al, 2017; Warren et al, 2013), which led to the hypothesis of cortico‐striato‐thalamo‐cortical pathways dysregulation in OCD (Carlisi et al, 2017; Milad & Rauch, 2012; Norman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that this increase in P3 amplitude may be related to alterations in cognitive processing in OCD, particularly in the context of attention and stimulus evaluation. Increased P3 amplitude in OCD patients may suggest that they are allocating more attentional resources to certain stimuli, which may contribute to the excessive repetitive behaviors and intrusive thoughts characteristic of the disorder ( Chang et al, 2013 ; Raggi et al, 2021 ). Some studies investigated the brain response to cholecystokinin-tetrapeptide (CCK-4), a compound that induces panic attacks in susceptible individuals, in patients with OCD and healthy control groups.…”
Section: Discussionmentioning
confidence: 99%